Case report: Transvaginal single-port extraperitoneal laparoscopic sacrospinous ligament fixation for apical prolapse: A single-center case series - Liu, Ye; Wang, Chao; Wang, Xianjing; Yan, Rongrong; Chu, Lei; Chen, Xinliang (Frontiers in Surgery, 2023)
ABSTRACT Background: Sacrospinous ligament fixation (SSLF) is a minimally invasive and effective procedure for the treatment of apical prolapse. Because intraoperative exposure of the sacrospinous ligament is difficult, SSLF is difficult. The aim of our article is to determine the safety and feasibility of single-port extraperitoneal laparoscopic SSLF for apical prolapse. Methods: This single-center, single-surgeon case series study included 9 patients with pelvic organ prolapse quantification (POP-Q) III or IV apical prolapse who underwent single-port laparoscopic SSLF. Additionally, transobturator tension-free vaginal tap (TVT-O) was performed in 2 patients, and anterior pelvic mesh reconstruction was performed in 1 patient. Results: The operative time ranged from 75~105 (mean, 88.9±10.2) min, and blood loss ranged from 25~100 (mean, 43.3±22.6) ml. No serious operative complications, blood transfusions, visceral injuries, or postoperative gluteal pain were reported for these patients. After 2~4 months of follow-up, no recurrence of POP, gluteal pain, urinary retention/incontinence, or other complications was observed. Conclusion: Transvaginal single-port SSLF is a safe, effective, and easy-to-master operation for apical prolapse.